2020
DOI: 10.1111/bjh.16751
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue in children and adolescents with immune thrombocytopenia

Abstract: Immune thrombocytopenia (ITP), an acquired autoimmune disorder of low platelets and risk of bleeding, has a substantial impact on health-related quality of life (HRQoL). Patients with ITP often report significant fatigue, although the pathophysiology of this is poorly understood. In this observational cohort of 120 children receiving second-line therapies for ITP, we assessed reports of fatigue using the Hockenberry Fatigue Scale. Children and adolescents with ITP reported a similarly high level of fatigue wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 28 publications
3
40
0
2
Order By: Relevance
“…Several factors including frequent hospitalizations, therapy side effects, limitations in social activities, iron deficiency from bleeding, and the perception of parental anxiety should be all considered as potential causes of poor HRQoL in children with ITP 15,22,41 . Our findings appear similar to those observed in adults affected by ITP, 31 and confirm earlier reports from pediatric studies 20,21 . Sarpatwari et al in a study conducted on 696 adults and 94 children with ITP showed that 12.5% and 8%, respectively, experienced fatigue.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Several factors including frequent hospitalizations, therapy side effects, limitations in social activities, iron deficiency from bleeding, and the perception of parental anxiety should be all considered as potential causes of poor HRQoL in children with ITP 15,22,41 . Our findings appear similar to those observed in adults affected by ITP, 31 and confirm earlier reports from pediatric studies 20,21 . Sarpatwari et al in a study conducted on 696 adults and 94 children with ITP showed that 12.5% and 8%, respectively, experienced fatigue.…”
Section: Discussionsupporting
confidence: 88%
“…Towner et al reported fatigue in 70% of pediatric patients affected by ITP 20 . Subsequently, Grace et al confirmed these results 21 . Our study quantitatively assesses fatigue in children with chronic ITP and their caregivers, using a validated, standardized, and age‐appropriate instrument.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations